2017
DOI: 10.1002/mc.22717
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐492 overexpression involves in cell proliferation, migration, and radiotherapy response of cervical squamous cell carcinomas

Abstract: MicroRNAs (miRNAs) are small non-coding RNA that target protein-coding mRNAs at the post-transcriptional level. The aim of this study was to define the role of miR-492 in cervical squamous cell carcinomas. After microRNA profiling and comparison, we firstly detected miR-492 expression in 104 tumor tissues biopsies derived from advanced staged (FIGO IIB-IIIB) cervical squamous cell carcinoma patients before receiving concomitant chemoradiotherapy and found miR-492 expression was significantly higher in the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…miR-492 is aberrantly expressed in several types of human cancer. For example, miR-492 is downregulated in cervical cancer tissue specimens and cell lines (20). miR-492 downregulation is significantly correlated with the pelvic lymph node metastasis of patients with cervical cancer (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-492 is aberrantly expressed in several types of human cancer. For example, miR-492 is downregulated in cervical cancer tissue specimens and cell lines (20). miR-492 downregulation is significantly correlated with the pelvic lymph node metastasis of patients with cervical cancer (20).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miRNAs may serve as potential diagnostic biomarkers and therapeutic targets for patients with RB. miR-492 is reportedly downregulated in cervical cancer (20), osteosarcoma (21) and clear cell renal cell carcinoma (22). By contrast, miR-492 is upregulated in hepatoblastoma, hepatic cancer (23) and breast cancer (24).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is clear that MMP develops a pleiotropic effect on tumor installation by remodeling ECM and activating signaling molecules, impacting cell adhesion and metastatic phenotype ( Figure 5). [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Studies suggested that MMPs are involved in initial step of ECM degradation during metastatic process. 5,22,40,72…”
Section: Mmps Timps Referencesmentioning
confidence: 99%
“…Xiao, et al 93 (2015) Figure 5-Summary of the miRNAs effect over MMPs in some diseases [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Updating the role of matrix metalloproteinases in mineralized tissue and related diseases J Appl Oral Sci. 2019;27:e20180596 9/14 also important in genes encoding MMPs and they lead to changes in MMP expression patterns in cancer.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The previous studies has reported that miR-492 was involved in the development of some cancers, such as cervical squamous cell carcinomas [21], hepatoblastoma [22] and colon cancer cells [23]. We chose different types of cancer cell lines to detect the expression of miR-492.…”
Section: Mir-492 Promoted the Cell Proliferation Of Endometrial Cancementioning
confidence: 99%